A survey on the status of reference and information services in four high school libraries in Quezon City - Dery, Dorothy S. (1993)
This study analyzed the efficiency and effectiveness of Reference and Information Services of the high school libraries of Ateneo de Manila High School, Miriam College Foundation Incorporated High School, Philippine Science High School, and the University of the Philippines Integrated School. Using a questionnaire, it examined the date of establishment of the four high schools, number of student enrolment and faculty members during the School Year 1992-1993, location of the high school libraries, library collection, reference collection, type and number of reference queries, and library activities to encourage students and teachers to come to the library and use its resources, especially the reference materials.